Resonance effect in chatter formation in metal cutting - Amin, A. K. M. Nurul; Patwari, Muhammed Anayet Ullah (LAP Lambert Academic Publishing, 2011)
Machine tool chatter is a type of intensive self-excited vibrations of individual components of Machine-Tool-Fixture-Work (MTFW) system. Chatter causes unwanted excessive vibratory motion in between the tool and the work-piece causing adverse effects on the product quality and machine-tool and tool life. In addition to the damage of the work-piece surface due to chatter marks, the occurrence of severe chatter results in many adverse effects, which include poor dimensional accuracy of the work-piece, reduction of tool life, and damage to the machine. There are many sources of vibration in the machine tools, like unbalanced rotating forces in the drives of the machine tools, transmission of vibrating forces from neighbourhood to jobs and tools, fluctuations in the cutting forces, variable chip thickness, chip formation instability etc. causing self-excited vibration. However, it needs to be mentioned that chatter is not the only vibration phenomenon during practical cutting conditions; there are other forms of vibration evident in metal cutting, which include free vibration and forced vibration. These vibrations do not pose any fundamental problems to the machinist because when the sources of the problem have been identified, they can be eliminated, at least in theory if not always practically. This just goes to show that in engineering the gap between theoretical knowledge and practical application is often difficult to bridge (Tobias 1965). Though the application of certain conservative cutting parameters may help to avoid chatter but that would lead to loss of productivity. As high productivity has become important in many applications, the industry has started seeking for less conservative chatter-free cutting parameters not to compromise with the material removal rate. Although chatter stability limits for certain cutting conditions can be found through experiments, they are, however, time-consuming and expensive. As an alternative, a theoretical model considering the dynamics in machining processes can be more costeffective and efficient than the experimental approach. Hence the development of a reliable chatter model can significantly contribute to achieving high productivity in machining operations. Although the phenomenon of chatter has been extensively investigated over the past 100 years but most of the research works were concentrated on the basic theory of chatter, or the role of the structural dynamics of the machine tool on chatter. The phenomenon was not looked at from the perspective of interaction between the inherent instabilities of the chip formation process during metal cutting and the natural vibrations of the elastic system components of the machine tool. Hence there is a need for in-depth understanding of the chatter phenomena, its inherent nature, the causes of its formation, the factors that influence its appearance and help in maintaining it and the possible ways of avoiding its occurrence during metal cutting the methods of chatter suppression. An attempt has been made in this book to present first the basic understandings on the metal cutting process and the methods of investigation of chip and the chip-tool contact processes. The existing classification of the chips has been reviewed and a new classification is presented. The instabilities of chip formation under different cutting conditions has been looked into more carefully with special emphasis on the serrated chips, since most chatter problems in metal cutting are believed to be related to serrated chip formation. The causes and mechanisms of serrated chip formation have also been included. Classification of serrated chips, the frequencies of their formation and methods of determining these frequencies have been discussed. Since the machine-tool-work-fixture is considered to be a closed loop system, any form of vibration appearing during metal cutting would involve vibration of any one or more of the components of this system. Hence, the prominent mode (natural) frequencies of the system are considered to be important and these will be discussed in detail and the behavior of the system under cutting and non cutting conditions will be presented. The main objective of the book will be to present convincingly the interaction between the inherent instabilities of the chip formation process and the natural vibrations of the prominent system components to explain the causes of formation chatter in different cutting speed ranges and in cutting different metals and alloys under wide variety of cutting conditions. This is believed to establish a new understanding on the mechanism of chatter formation based on the proposed ‘resonance’ concepts of chatter formation as opposed to the existing ‘regenerative’ chatter concept.